Organizing Accounting in Markets (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article discusses the organization of accounting in markets and its significance in detail. In the context of a market economy, an efficient accounting system plays a crucial role, as it is necessary for monitoring the financial status of a company and making strategic decisions. This article provides comprehensive information about the main approaches to organizing accounting in markets, practical examples, and successful experiences of large companies.